Regulative Aspects of Public Services in Slovenia - Mik STRMECKI (Transylvanian Review of Administrative Sciences, 2006)
The main points tackled in this paper are the evolution of regulation of public services and the way in which they are provided in Slovenia from the advent of the so-called transition period up to the present. The importance of this sort of regulation is to create a level playing field between the private and public sectors to function to their utmost mutual advantage and at the same time safeguarding the public interest. The paper further addresses also the objectives of regulation in this field such as promoting healthy competition, the creation of a level playing field for competition to play itself out properly and in congruity with the law and also in such a way as to prevent unjustified profiteering, monopolistic abuses etc. The paper also touched upon the functional characteristics of the regulating authority, appointment procedures, funding and the regulatory process. The focus of the paper is on the public service delivery landscape in our country: the direct provision by the central government or local government and the indirect service delivery, which has numerous sub-forms such as public companies, concessionary public service and publicprivate partnerships.